Introduzione - Fichera, Francesca (Kritik. Rivista di letteratura e critica culturale, 2024)
Jean Giraudoux, French writer and diplomat, is best known in Italy as a playwright. However, he also dedicated himself to fiction: indeed, his novel Scelta delle Elette represents a profound analysis of the marital crisis and the human condition. The main character, Édmée, abandons her family, triggering an unsolvable crisis. Her escape and her relationships with the other characters of the novel reflect a desire for separation from the male world, without however offering decisive solutions. Written between 1938 and 1939, in a context of growing historical oppression, the work represents an escape from the anguish of reality, sublimated in lyrical and evocative prose: therefore, this Italian translation of Choix des Élues aims to enhance this lesser-known dimension of Giraudoux’ production, highlighting its literary depth and relevance.